2005
DOI: 10.1074/jbc.r400035200
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Cyclic GMP-dependent Protein Kinases

Abstract: Basic Properties of cGMP-dependentProtein Kinase Isoforms cGKs 1 belong to the family of serine/threonine kinases and are present in a variety of eukaryotes ranging from the unicellular organism Paramecium to Homo sapiens (1, 2). Mammals have two cGK genes, prkg1 and prkg2, that encode cGKI and cGKII. The N terminus (the first 90 -100 residues) of cGKI is encoded by two alternatively spliced exons that produce the isoforms cGKI␣ and cGKI␤. The enzymes have a rod-like structure and are activated at submicromola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
194
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(197 citation statements)
references
References 87 publications
(89 reference statements)
2
194
0
1
Order By: Relevance
“…Pharmacological and genetic studies have indicated that cGMP could be the central mediator of the effects NO͞cGMP in several brain regions (41)(42)(43). cGMP has several target proteins, including cGMP-regulated cation channels and cGMPdependent PKs.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological and genetic studies have indicated that cGMP could be the central mediator of the effects NO͞cGMP in several brain regions (41)(42)(43). cGMP has several target proteins, including cGMP-regulated cation channels and cGMPdependent PKs.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO), the most important endogenous vasodilator, regulates VSMC relaxation by increasing intracellular cGMP and activating cGMP-dependent kinase I (PKGI) (7,8). The two isoforms of PKGI, PKGI␣ and PKGI␤, are identical except for their amino termini, which contain different leucine zipper (LZ) heptad repeat motifs that are critical for protein targeting (9).…”
mentioning
confidence: 99%
“…These mice are terminally ill when born (the majority die before 6 weeks of age) and have multiple cardiovascular, gastrointestinal, hematopoietic, and neurological defects that preclude complete investigation of most cardiovascular functions, including blood pressure (13,23). PKGI␣ and PKGI␤ both regulate VSMC tone through interactions with key VSMC contractile proteins mediated by their respective LZ domains (10,16,17,24). PKGI␣ promotes vascular relaxation by regulation of the two major VSMC pathways regulating contractile state.…”
mentioning
confidence: 99%